ANALISIS KONSUMSI DI INDONESIA TAHUN 1989 - 2002 (TINJAUAN TERHADAP HIPOTESIS KEYNES DAN POST KEYNES) - Isyani, Isyani; Hasmarini, Maulidyah Indira (Universitas Muhammdaiyah Surakarta, 2005)
Consumption expenditure of Indonesian society encompasses 60 percent until 70 percent from GNP in Indonesia. Based on Post Keynes and Keynes hypothesis, the research investigated consumption pattern of Indonesian society by partial adjustment method of regression. By this regression method, balance adjustment model in long and short term can be estimated. Research period used is from 1989 until 2002 with the quarterly data. Variables which supposed influencing consumption of society and they are used in model in addition to national income are real interest rate, stock investment, money in circulation, and income tax. The result of this research showed that MPC is 0,8337, therefore it needs doing the effort to decrease MPC or at least to keep the value.